2013
DOI: 10.1159/000353878
|View full text |Cite
|
Sign up to set email alerts
|

Array-CGH Analysis Suggests Genetic Heterogeneity in Rhombencephalosynapsis

Abstract: Rhombencephalosynapsis is an uncommon, but increasingly recognized, cerebellar malformation defined as vermian agenesis with fusion of the hemispheres. The embryologic and genetic mechanisms involved are still unknown, and to date, no animal models are available. In the present study, we used Agilent oligonucleotide arrays in a large series of 57 affected patients to detect candidate genes. Four different unbalanced rearrangements were detected: a 16p11.2 deletion, a 14q12q21.2 deletion, an unbalanced transloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Several of these rearrangements are recurrently observed in cases of intellectual disability, such as 2.6 Mb-microdeletion of 22q11.21 (proximal deletion) corresponding to DiGeorge syndrome (Burnside, 2015), 16p11.2 microduplication that confers susceptibility to autism (Fernandez et al, 2010), 16p13.11 encompassing the NDE1 gene involved in brain neurogenesis and rhombencephalosynapsis (Bakircioglu et al, 2011;Démurger et al, 2013) and 15q11.2 microdeletion emerging as one of the most common cytogenetic abnormalities in intellectual disability and autism spectrum disorder (Butler, 2017). These deletions and duplications are thus at the origin of other neurodevelopmental disorders but are not sufficient to fully explain HPE.…”
Section: Chromosomal Abnormalities and Copy Number Variants In Hpementioning
confidence: 99%
“…Several of these rearrangements are recurrently observed in cases of intellectual disability, such as 2.6 Mb-microdeletion of 22q11.21 (proximal deletion) corresponding to DiGeorge syndrome (Burnside, 2015), 16p11.2 microduplication that confers susceptibility to autism (Fernandez et al, 2010), 16p13.11 encompassing the NDE1 gene involved in brain neurogenesis and rhombencephalosynapsis (Bakircioglu et al, 2011;Démurger et al, 2013) and 15q11.2 microdeletion emerging as one of the most common cytogenetic abnormalities in intellectual disability and autism spectrum disorder (Butler, 2017). These deletions and duplications are thus at the origin of other neurodevelopmental disorders but are not sufficient to fully explain HPE.…”
Section: Chromosomal Abnormalities and Copy Number Variants In Hpementioning
confidence: 99%
“…Autism was diagnosed in a patient with partial rhombencephalosynapsis (22). Chromosomal mutations in particular cases of rhombencephalosynapsis are associated with autism (23). Evidently, cerebellar malformation is responsible for autistic symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported chromosomal rearrangements in patients with RES (Table II), though no recurrent copy number variants have emerged (Demurger et al, 2013; di Vera et al, 2008; Lespinasse et al, 2004; Pasquier et al, 2009; Ramocki et al, 2011; Truwit, Barkovich, Shanahan, & Maroldo, 1991). Partial RES was reported in one of 5 individuals with a de novo mutation in the CHAMP1 gene, but limited neuroimaging data were reported to substantiate this diagnosis (Hempel et al, 2015) and mutations in this gene have not been identified in other individuals with RES.…”
Section: Evidence For Genetic Basismentioning
confidence: 99%